Metafora dalam Naskah Drama "Senja dengan Dua Kelelawar" Karya Kirdjomulyo - Hidayah, Alfia Nurul; Oktavia, Wahyu (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2019)
This study aims to describe the type of metaphor in the drama  script Senja dengan Dua Kelelawar. This study uses a type of qualitative descriptive research where unbound places analyze the form of descriptions that are not in the form of numbers or coefficients about the relationship of variables. The method used is content analysis by examining the contents of a document. In this study the document in question is a drama script Senja dengan Dua kelelawar. The data collection technique used in this research is the observation and note technique, because the data is in the form of text. The data analysis technique uses data reduction, data presentation and verification. Based on data analysis carried out on the drama Senja dengan Dua Kelelawar by Kirdjomulyo, it contains four types of metaphoric language styles according to the Parera theory consisting of 9 data anthropomorphic metaphors, 3 animal metaphor data, 7 data abstract to concrete metaphors, and 4 data synesthesia metaphors.Keywords: semantics; metaphor; drama script.